ANALISIS PENGARUH PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IX-A SMP IT BUDI LUHUR CIMAHI PADA MATERI TRANSFORMASI - Nurrohmah, Siti; Maya, Rippi; Afrilianto, M. (IKIP Siliwangi, 2023)
Research with a scientific approach in an effort to help students' mathematical understanding of grade IX SMP in transformation material has the aim of analyzing the effect of the scientific approach on students' mathematical understanding ability on transformation material (reflection). In this study, the type of classroom action research was used, with the research subjects with the criteria being students of class IX-A SMP IT Budi Luhur Cimahi. The number of samples used were 21 students for 2 cycles. The analysis was carried out with test and non-test instruments, giving questions as research test instruments consisting of 5 pre-test and post-test questions in the form of descriptions that will measure students' mathematical understanding abilities. While the non-test instrument is a questionnaire scale of 15 statements given to students to measure students' self-confidence. The data processing technique for the test instrument used is the N-Gain analysis test, while for the non-test instrument, Microsoft excel is used. The results showed that the scientific approach affected the mathematical understanding ability of class IX-A students with average criteria with a value of 0.55. The average value of the pretest is 3.86 and the average value of the posttest is 12.71. Based on these data, there was an increase in the value of 8.86, while the average value of the questionnaire was 68.41%, meaning that it had a strong effect on students' self-confidence.